Comparative Migration Studies - Roohi, Sanam; Scholten, Peter; Saharso, Sawitri; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Comparative Migration Studies (CMS) is an international, peer-reviewed open access journal that provides a platform for articles that focus on comparative research in migration, integration, and race and ethnic relations. It presents readers with an extensive collection of comparative analysis, including studies between countries, groups, levels, and historical periods. CMS publishes research based on qualitative, quantitative, and mixed methods studies. Contributions cover a wide disciplinary angle across the social sciences and the humanities. We are looking for articles that push present understanding of migration integration, and race and ethnic relations in new conceptual, methodological, and empirical directions. Topics include, but are not limited to: migration and integration in relation to citizenship, national identity, refugee and asylum policy, social movements (pro and anti-immigration), gender, racialization, whiteness, ethnic and religious diversity and (post)colonialism. .
Keywords: Demography; Population; Sociology; Population$1 (BEconomic aspects.s; Population and Demography; Sociology; Population Economics